Pengembangan Usaha Mikro Industri Kreatif "Kerupuk Ikan" - Judi Suharsono; Hosnol Wafa (Jurnal ABM Mengabdi, 2017)
Some communities in Coastal Probolinggo have a business in making fish crackers. Fish crackers as home business (home industry) is a reliable livelihood to support everyday life. The problems faced by partners are the absence of equipment mixer and semi-automatic fish crackers and the condition is still manual, the use of unstructured accounting records and management has not been well ordered. The goal in this IbM activity is to improve the quality and quantity of fish crackers in order to meet the growing market demand. The method used in IbM activities is the substance of science and technology and training. The outputs generated in IbM activities are dough mixer machine, fish cracker cutting machine, management training and accounting